Strategies for Improving Traditional Food Safety “Urutan” Chicken through the Implementation of GMP and SSOP - A.A. Made Semariyani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
In the traditional “Urutan” chicken production process, the type and quality of raw materials and additional materials vary widely. In addition, other factors such as environmental conditions are difficult to control, and also the uncertain endpoint of the process involved, thus the application of basic feasibility needs to be done to improve the quality of the product. In this study, a model for the application of GMP (Good Manufacturing Practice) and (Sanitation Standard Operating Procedures) was developed for the production of 'Urutan' chicken. Analysis of the chemical, microbiological and organoleptic components was carried out based on the quality and food safety of meat sausage (SNI 3820-1-2015). According to analysis results, it was revealed that the implementation of GMP and SSOP was poorly implemented. This was proven from the results of the analysis of the product from producers number 6 and 8 that did not meet the requirements of Total Plate Count (TPC) meat sausage (SNI 3820-1-2015) because it exceeded the requirements of 1 x 105 which from the test results obtained 2.5 x 106 colonies/ g and 5.5 x 106 colonies/g. That indicated that sanitation and hygiene were inadequate. Meanwhile, the organoleptic assessment of color resulted (slightly like - very like), texture (rather dislike - extremely like), aroma (rather dislike - like), taste (neutral – extremely like), and overall acceptance (neutral to very like).